Informed Amidst Isolation: Examining the Lampung Province People ‘s Information and Media Literacy During the Covid-19 Pandemic - Andi Windah,; Ida Nurhaida,; Nina Yudha Aryanti, (Literatify : Trends in Library Developments, 2023)
The Covid-19 pandemic which has lasted more than 3 years has positioned Covid-19 information on the media agenda. Apart from that, this pandemic has also changed the social order which has resulted in increased ownership, media access and communication effects. In the process, the communication effect is related to the level of media literacy regarding Covid-19 information which is on the media agenda. The formulation of the problem in this research is how high the level of media and information literacy for Covid-19 is in Lampung province. This research is examined through agenda setting theory, social category theory and stages of media literacy. The research method used is quantitative descriptive. The sampling technique used in this research is cluster sampling. Based on Yamane's formula, a sample of 100 people was determined. By using cluster sampling, the respondents for this study were represented by 20 respondents each from 5 districts in Lampung Province. The research results show that the level of media and information literacy for Covid-19 is 52.45% or is in the medium category. The results are understandable as the extensive reporting on COVID-19 over three years has enhanced public information literacy, encompassing various aspects from information needs to sharing capabilities. However, disparities in information reception exist due to factors like the shift from personal to media interactions because of mobility restrictions, the public's unpreparedness for the pandemic's impacts which reprioritized media access needs, and demographic factors like education and economic levels influencing information acceptance.